The Relationship Between Peer Social Support and Academic Stress Among University Students During the COVID-19 Pandemic: [Hubungan Antara Dukungan Sosial Teman Sebaya dan Stres Akademik Mahasiswa Selama Pandemi COVID-19] - Prayitno, Hayyu Aliya; Andayani, Budi (Faculty of Psychology, Universitas Surabaya, 2023)
The sudden transition of the learning environment during the COVID-19 pandemic brings many challenges for university students, potentially leading them to experience higher levels of academic stress. Previous studies have found that peer social support is beneficial to help students deal with academic stress. Therefore, this study aims to find the relationship between peer social support and academic stress among university students during online learning. Peer Social Support Scale and Academic Stress Scale were used as instruments for data collection. A total of 230 undergraduate students from 14 universities in Yogyakarta, Indonesia participated in the study. The participants were students who currently or had attended lecture(s) in the time of learning transformation from physical (face-to-face) to virtual (distance) environment due to social restrictions. A simple linear regression technique was applied to evaluate academic stress as a function of peer social support. This study found that students who receive peer social support experienced lower levels of academic stress during online learning. Further suggestions for students, educational practitioners, and educational institutions were also discussed. Perubahan lingkungan belajar yang tiba-tiba selama pandemi COVID-19 menyebabkan banyak tantangan untuk mahasiswa, dan berpotensi meningkatkan tingkat stres akademik. Sejumlah studi terdahulu menemukan bahwa dukungan sosial teman sebaya berperan membantu mahasiswa mengatasi stres akademik. Maka dari itu, studi ini bertujuan untuk mencari hubungan antara dukungan sosial teman sebaya dan stres akademik pada mahasiswa selama pembelajaran daring. Peer Social Support Scale dan Academic Stress Scale digunakan untuk pengambilan data. Terdapat total 230 mahasiswa dari 14 universitas di Yogyakarta, Indonesia yang berpartisipasi dalam studi. Partisipan adalah mahasiswa aktif yang sedang atau pernah mengikuti perkuliahan selama transisi proses belajar dari pembelajaran tatap muka ke pembelajaran virtual akibat pembatasan sosial. Analisis regresi linear sederhana digunakan untuk mengkaji stres akademik sebagai fungsi dari dukungan sosial teman sebaya. Studi ini menemukan bahwa mahasiswa yang mendapatkan dukungan sosial teman sebaya akan mengalami tingkat stres akademik yang lebih rendah selama pembelajaran daring. Studi ini juga mendiskusikan saran lebih lanjut yang diharapkan dapat berguna untuk mahasiswa, praktisi pendidikan, dan institusi pendidikan.